STUDI TINGKAT PENYALAHGUNAAN NARKOBA PADA PELAJAR SLTA (SMA/SMK) DI KABUPATEN TABANAN - Laksmiani, Ni Putu Linda; Sulastini, Ni Putu Eka (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2014)
The level of drug abuse and drug knowledge among senior high school students in Tabanan regency has been assessed. A simple random sampling method was used to select the students. Under 90% confidence level was obtained 270 students, who involved in this study. The students were asked to answer the questionnaire to find out their knowledge of drug abuse effects. They also followed a urine screen test using rapid EMIT-test for the amphetamine, methamphetamine, opiate, cocaine, cannabis and benzodiazepine. More than 95% of students had a bad level knowledge of drug abuse effect. We found out a positive correlation between frequency students to access drug information online and attending drug-abuser prevention course to their knowledge. Base on screen test was found out just one student positive to benzodiazepine.
Keywords: drugs; knowledge; drug abuse; student; Tabanan